PENGARUH LAPISAN HIDROFOBIK PADA PERMUKAAN ISOLATOR POLIETILEN TERHADAP TINGKAT ARUS BOCOR DAN TEGANGAN FLASHOVER PADA VARIASI PAPARAN SINAR ULTRAVIOLET - n/a Rizaq; Moch. Dhofir; Teguh Utomo (Jurnal Mahasiswa TEUB, 2022)
This study discusses the effect of the hydrophobic layer on the surface of the polyethylene insulator on the leakage current and flashover voltage with variations in exposure to ultraviolet light. This research was conducted by varying the conditions of ultraviolet irradiation on the insulator, test voltage, and also the test conditions in the form of dry and wet conditions. Variations in the duration of ultraviolet irradiation were for 0 hours, 24 hours, and also 48 hours. The insulator used is also divided into 2, an insulator with coating and a non-coating. Initial testing of the contact angle to determine whether the insulator is hydrophobic. Furthermore, distribution simulations and electric field efficiency calculations were carried out using FEMM 4.2 software, so that dielectric strength values could be calculated. After that, leakage current and flashover tests were carried out with voltage variations of 4kV, 8kV, 12kV, 16kV, and 20kV. The results obtained in this study are the greater the value of the test voltage given, the greater the value of the leakage current, while the flashover voltage has an inverse relationship with the leakage current. The greater the leakage current, the smaller the flashover voltage. In insulators with a hydrophobic layer, the value of the leakage current and flashover voltage can be improved. In addition, the addition of the duration of irradiation causes the value of the leakage current to be greater and the flashover to decrease in value.Keywords— insulator, leakage current, flashover, hydrophobic, polyethylene